Decision making in team sports: analysis of determinant factors and methodologies of training - Tessitore, A. (23rd International Scientific Conference "FIS COMMUNICATION 2021", 2021)
In addition to a high level of physical and physiological conditions, to succeed in team sports require players to possess a high level of technical and tactical skills. Decision making is the process through which players choose what they will do in a play, mainly to support the tactical component of the game. It impacts on the performance through two dimensions: individual solutions generated in the moment of the action (reading the play) and collective strategy (pre]deterined solutions). In particular, the variability and unpredictability characteristics of actions, require team sports players to continuously take successful decisions in the play in both ball possession and not possession conditions (Grehaigne, Godbout, & Bouthier, 1997). To have an idea of the flow of decision has been estimated that a normal person makes about 6000 decisions throughout the day while a football player usually makes more than 2500 decisions during a single match (Teoldo, Guilherme, & Garganta, 2017). In some instances, the choice may be simple, based on a yes-onot context, in others be more complex. The more players are skilled, the more they are able to extrapolate and process information from the competitive environment in order to identify salient, predictive, global cues within the context of the play and their intended goal. In addition to expertise, and other covariables that influence the quality and accuracy of decisions, mental fatigue can play a relevant role (Kunrath, Nakamura, Roca, Tessitore, & Teoldo Da Costa, 2020). It has been reported that mental fatigue compromises the ability to maintain attention on what is important during a task, compromising focus, performance adjustment, rapid and accurate reaction, and interpretation of meaningful cues in the visual field, as well as reducing technical performance (Coutinho, Goncalves, Wong, Travassos, Coutts, & Sampaio, 2018). Among other well-known factors, a related decision making training might include: a) to play exploring different degrees of freedom, b) to elicit eliciting reinvestment by leaving room for mistakes (Petiot, Bagatin, Aquino, & Raab, 2021).